Koncepcja uwagi wizualnej - Młodkowski, Jan (Acta Universitatis Lodziensis. Folia Psychologica, 2008)
According to the general theory of attention the selective function creates the perceptive and cognitive fractions. Conversely the controlling function creates behavioural and immanent fractions. Particular connection with visual attention has the perceptive function. It as two types such as an exploratory attention and as a penetrative attention. Former guides the process of focusing areas of retina with an existing image onto the central area ranking them accordingly with their physical properties such as density, contrast, motion, etc. The penetrative attention constantly creates a program of an object’s identification comprised of memory imprints and current spacial relation between the observed object and the observing eye. The cognitive attention supports only processing of imagering. It doesn’t involve oculomotoric activity. The full text of the article explores as well relationships between visual attention and phenomenons of classic psychology: Perky’s effect, eidetic imagery and alternative figures and silhouettes.